SATJIPTO RAHARJO DAN KRITIKNYA TERHADAP EKONOMI KOLONIALISME - Andi Tri Haryono (Jurnal Hukum Progresif, 2009)
Colonialism under Dutch rule constitutes one of the darkest periods in Indonesian history, marked by widespread suffering resulting from exploitative economic policies, particularly the cultuurstelsel (Cultivation System). This article examines economic colonialism from two main perspectives. First, it analyzes the discourse of classical liberal economic thinkers, including Adam Smith, David Ricardo, Thomas Malthus, Jean-Baptiste Say, and John Stuart Mill, whose ideas on free trade and economic prosperity were frequently used to justify colonial expansion and the exploitation of overseas territories. Such ideological foundations legitimized commercial and territorial expansion by Western powers, resulting in profound social and economic consequences for colonized regions in Asia, Africa, and South America. Second, the article argues that contemporary economic colonialism has re-emerged in a different form through the growing influence of multinational corporations (MNCs). Their dominance in market mechanisms, organizational structures, human resource management, operations, and marketing has significantly shaped national economies. In Indonesia, the expansion of MNCs has intensified market concentration and posed substantial challenges to domestic enterprises and indigenous entrepreneurs. The article concludes that although the forms of colonialism have changed, economic domination remains a persistent feature of global capitalism.